Eaf1 Links the NuA4 Histone Acetyltransferase Complex to Htz1 Incorporation and Regulation of Purine Biosynthesis - Cheng, Xue (Eukaryot Cell, 2015)
Proper modulation of promoter chromatin architecture is crucial for gene regulation in order to precisely and efficiently orchestrate various cellular activities. Previous studies have identified the stimulatory effect of the histone-modifying complex NuA4 on the incorporation of the histone variant H2A.Z (Htz1) at the PHO5 promoter (A. Auger, L. Galarneau, M. Altaf, A. Nourani, Y. Doyon, R. T. Utley, D. Cronier, S. Allard, and J. Côté, Mol Cell Biol 28:2257–2270, 2008, http://dx.doi.org/10.1128/MCB.01755-07). In vitro studies with a reconstituted system also indicated an intriguing cross talk between NuA4 and the H2A.Z-loading complex, SWR-C (M. Altaf, A. Auger, J. Monnet-Saksouk, J. Brodeur, S. Piquet, M. Cramet, N. Bouchard, N. Lacoste, R. T. Utley, L. Gaudreau, J. Côté, J Biol Chem 285:15966–15977, 2010, http://dx.doi.org/10.1074/jbc.M110.117069). In this work, we investigated the role of the NuA4 scaffold subunit Eaf1 in global gene expression and genome-wide incorporation of Htz1. We found that loss of Eaf1 affects Htz1 levels mostly at the promoters that are normally highly enriched in the histone variant. Analysis of eaf1 mutant cells by expression array unveiled a relationship between NuA4 and the gene network implicated in the purine biosynthesis pathway, as EAF1 deletion cripples induction of several ADE genes. NuA4 directly interacts with Bas1 activation domain, a key transcription factor of adenine genes. Chromatin immunoprecipitation (ChIP) experiments demonstrate that nucleosomes on the inactive ADE17 promoter are acetylated already by NuA4 and enriched in Htz1. Upon derepression, these poised nucleosomes respond rapidly to activate ADE gene expression in a mechanism likely reminiscent of the PHO5 promoter, leading to nucleosome disassembly. These detailed molecular events depict a specific case of cross talk between NuA4-dependent acetylation and incorporation of histone variant Htz1, presetting the chromatin structure over ADE promoters for subsequent chromatin remodeling and activated transcription.